2020
DOI: 10.1103/physreva.102.033113
|View full text |Cite
|
Sign up to set email alerts
|

Phase-matching analysis in high-order harmonic generation with nonzero orbital angular momentum Laguerre-Gaussian beams

Abstract: Through high-order harmonic generation driven by intense ultrashort vortex infrared or midinfrared lasers, a nonzero orbital angular momentum can be imprinted onto extreme ultraviolet (XUV) or soft-x-ray (SXR) light pulses. Here we simulate the generation of vortex XUV harmonics in the gas medium as well as their propagation in vacuum till reaching the far field. We find that the intensity and phase of generated high harmonics are very sensitive to the position of gas jet with respect to the laser focus. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 65 publications
4
17
0
Order By: Relevance
“…To simulate the vortex HHG driven by the mixed LG beams, we employ the general propagation theory in a gas medium, which has been established in Refs. [51,52]. Here we will only adopt some key equations, and will focus on the variation of spatial features of the mixed LG beams with the radial nodes.…”
Section: Theoretical Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To simulate the vortex HHG driven by the mixed LG beams, we employ the general propagation theory in a gas medium, which has been established in Refs. [51,52]. Here we will only adopt some key equations, and will focus on the variation of spatial features of the mixed LG beams with the radial nodes.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…We assume that the fundamental LG beams carrying orbital angular momentum (OAM) remain unchanged while propagating through an ionized gas medium, resembling their behaviors in free space. The propagation characteristics of the vortex high-harmonic field in the ionizing medium can be described by (in a Cartesian coordinate) [51,52,58] ∇…”
Section: Propagation Equations Of High-harmonic Field In the Gas Mediummentioning
confidence: 99%
See 1 more Smart Citation
“…According to formula (1), the phases of each unit are calculated, and the phase shifts between adjacent units required for the first to the seventh OAM modes are shown in Table 1. Near-field phase distributions (Jin et al, 2020;Feng, Lin, and Long 2020) of this UCA are shown in Figure 3, where the observation plane of 300 mm × 300 mm large is set 300 mm away from the array aperture. Figure 4 (a) to (g) is the phase distribution diagrams of the first to the seventh-order vortex electromagnetic waves respectively.…”
Section: Uca Feed Systemmentioning
confidence: 99%
“…Subsequently, Liu et al also accomplished the ground-state cooling of the rotating mirror in a double L-G cavity with atomic ensemble [58]. These studies on the ground cooling of the rotating mirror have provided many opportunities to further investigate macroscopic quantum phenomena in rotational cavity optomechanical systems, including bipartite quantum entanglement [57,[60][61][62] and tripartite quantum entanglement [63], macroscopic quantum coherence [64], OMIT phenomena [65][66][67][68][69][70], and its applications for the measurement of orbital angular momentum [65,71,72], higher order sideband generation [73,74] and phase-matching analysis [75]. However, compared to studies on conventional optomechanical systems, the research on the double-OMIT phenomenon in this type of rotating cavity optomechanical system is still essentially very limited.…”
Section: Introductionmentioning
confidence: 99%